1997
DOI: 10.1128/jcm.35.11.2733-2739.1997
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of bacterial endocarditis by broad-range PCR amplification and direct sequencing

Abstract: Broad-range PCR amplification of part of the 16S rRNA gene followed by single-strand sequencing was applied to samples of 18 resected heart valves from patients with infective endocarditis. The PCR results were compared with those of cultures of valves and with those of previous blood cultures. For two patients there was agreement with the cultures of the valves; for nine patients there was agreement with the previous blood cultures, which were positive, while the cultures of the valves were negative; a Strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(102 citation statements)
references
References 36 publications
2
99
0
1
Order By: Relevance
“…Up to one-third of all cases of infective endocarditis are culture-negative [108], and diagnosis has relied mainly upon clinical and ultrasonographic findings. Goldenberger et al reported one of the earliest situations in which 16S rDNA PCR amplification and sequencing were performed on DNA extracted from infected valves [109]. Many subsequent studies confirmed the usefulness of the method [110][111][112][113][114][115][116][117][118][119].…”
Section: Detection Of Uncultivable Bacteria and Diagnosis Of Culture-mentioning
confidence: 99%
“…Up to one-third of all cases of infective endocarditis are culture-negative [108], and diagnosis has relied mainly upon clinical and ultrasonographic findings. Goldenberger et al reported one of the earliest situations in which 16S rDNA PCR amplification and sequencing were performed on DNA extracted from infected valves [109]. Many subsequent studies confirmed the usefulness of the method [110][111][112][113][114][115][116][117][118][119].…”
Section: Detection Of Uncultivable Bacteria and Diagnosis Of Culture-mentioning
confidence: 99%
“…While PCR product detection and analysis have typically been achieved using gel-electrophoresis and sequencing techniques, these approaches are laborious and timeconsuming, which detracts from clinical applicability. 139 The introduction of real-time PCR technology with the potential use of differentially labelled fluorescent probes for simultaneous identification of multiple amplified products in a single assay holds promise. 140 Unfortunately, current ability to spectrally differentiate multiple fluorescent signals is quite limited.…”
Section: Pcr-based Diagnosticsmentioning
confidence: 99%
“…ebi.ac.uk/Tools/sequence.html). Sequence homology identity was determined in accordance with criteria as described previously (25).…”
Section: Snp Detectionmentioning
confidence: 99%